Converting a Saul into a Paul in St. Cecily: or, The Converted Twins (1666): Pro-Catholic Polemics on the Early Restoration English Stage - Filip Krajník (Caliban: French Journal of English Studies)
The present discussion examines the little-known Restoration play St. Cecily: or, The Converted Twins (printed 1666 and 1667), attributed to the Catholic actor Matthew Medbourne. Although the play was probably never staged, even its publication in print could be considered as a striking declaration of a political manifesto. When St. Cecily was written, the English Catholic minority strove for tolerance, turning for help to political elites of the country, including the King, the Parliament and various members of the court. The play itself, dedicated to the Catholic Queen consort Catherine of Braganza, clearly partakes in the then current religious polemics, fighting anti-Catholic stereotypes that were ingrained in English society. While the political goal of the piece failed, St. Cecily remains an unusual testimony to the fragile political and religious situation in England in the early 1660s, as well as an example of the blurred boundaries between popular and “serious” works in terms of their ideological function.